Education psychology in context : readings for future teachers - Marlowe Bruce A. (editor); Canestrari Alan S. (editor) (Sage Publications, 2006)
This book of major readings in educational psychology provides a stimulating alternative for teachers wanting to understand how their students learn and develop by addressing the questions real teachers in real schools ask about real students.